Clinical Profile of Patients With Unilateral Sudden Sensorineural Hearing Loss: Correlation With Hearing Prognosis. (9th February 2021) - Perez Ferreira Neto, Adriana; da Costa Monsanto, Rafael; Dore Saint Jean, Line; Sonzzini Ribeiro de Souza, Lucas; de Oliveira Penido, Norma
Abstract : Objective: To characterize, with a standard systematic protocol, the clinical and audiometric profile of patients with idiopathic sudden sensorineural hearing loss (ISSNHL) and to correlate the findings with hearing recovery prognosis. Study Design: Retrospective cohort of patients with ISSNHL. Setting: Outpatients of a tertiary referral center followed for 20 years. Methods: We collected clinical information, including the presence of tinnitus, vertigo, and comorbidities, as well as initial pure tone averages, degree of hearing loss, audiogram curves, and time between hearing loss onset and treatment. These variables were statistically analyzed for their impact on hearing recovery prognosis. All patients were treated with oral corticosteroids, following a standard treatment protocol. Hearing recovery was defined according to the criteria of the American Academy of Otolaryngology–Head and Neck Surgery Foundation, and hearing outcomes were reported via a standardized method (scattergrams). Results: Our final study group comprised 186 patients. Most patients were between 41 and 60 years of age. Univariate analysis revealed that vertigo; presence of severe or profound initial hearing loss; flat, U‐shaped, and descending audiogram curves; and initiating treatment ≥15 days were correlated with worse hearing recovery. However, the multivariate logistic model revealed that only the presence of severe or profound hearing loss (odds ratio, 6.634; 95% CI, 2.714‐16.216; P <. 001) and initiating treatment ≥15 days (odds ratio, 0.250; 95% CI, 0.102‐0.610; P =. 008) were independent risk factors for worse hearing recovery prognosis. Conclusion: This study demonstrated that the presence of severe or profound hearing loss at the first audiogram and initiating treatment after 14 days from ISSNHL onset were independent risk factors associated with a worse hearing recovery prognosis.